Efficacy and safety of a proposed omalizumab biosimilar compared to the reference product in the management of uncontrolled moderate-to-severe allergic asthma: a multicenter, phase III, randomized, double-blind, equivalency clinical trial - Ghanei, Mostafa; Ghalebaghi, Babak; Sami, Ramin; Torabizadeh, Mehdi; Mirsadraee, Majid; Amra, Babak; Tavakol, Marzieh; Raji, Hanieh; Fallahpour, Morteza; Kiani, Arda; Abedini, Atefeh; Jabbari Azad, Farahzad; et al. (Frontiers in Immunology, 2024)
Background and aims Allergic asthma has a considerable burden on the quality of life. A significant portion of moderate-to-severe allergic asthma patients need omalizumab, an anti-immunoglobulin-E monoclonal antibody, as an add-on therapy. In this phase III clinical trial P043 (Zerafil®, CinnaGen, Iran) efficacy, safety, and immunogenicity were compared with Xolair® (the originator omalizumab). The primary outcome was the rate of protocol-defined asthma exacerbations. Methods Exacerbation rates, Asthma Control Test (ACT) results, spirometry measurements, immunogenicity, and safety were evaluated. Each subject received either medication with a dose ranging from 150 to 375 mg based on pre-treatment serum total IgE level (IU/mL) and body weight (kg) every two or four weeks for a duration of 28 weeks. Results Exacerbation rates were 0.150 (CI: 0.079-0.220) in the P043 group, and 0.190 (CI: 0.110-0.270) in the omalizumab group (per-protocol). The least squares mean differences of predicted Forced Expiratory Volume in the First second (FEV1) were -2.51% (CI: -7.17-2.15, P=0.29) and -3.87% (CI: -8.79-1.04, P=0.12), pre- and post-bronchodilator use. The mean ± SD of ACT scores at the screening and the last visit were 10.62 ± 2.93 and 20.93 ± 4.26 in P043 and 11.09 ± 2.75 and 20.46 ± 5.11 in the omalizumab group. A total of 288 adverse events were reported for the 256 enrolled participants. Among all, “dyspnea” and “headache” were the most reported ones. The overall incidence of adverse events (P=0.62) and serious adverse events (P=0.07) had no significant differences between the two groups. None of the samples were positive for anti-drug antibodies. Conclusion P043 was equivalent to omalizumab in the management of asthma in reduction of exacerbations. There was no significant difference in other efficacy and safety parameters. Clinical trial registration www.clinicaltrials.gov (NCT05813470) and www.IRCT.ir (IRCT20150303021315N20).